Predictors of length of stay in an acute psychiatric inpatient facility in a general hospital: a prospective study - Baeza, Fernanda L. (Braz J Psychiatry, 2017)
OBJECTIVE: There have been significant reductions in numbers of psychiatric beds and length of stay (LOS) worldwide, making LOS in psychiatric beds an interesting outcome. The objective of this study was to find factors measurable on admission that would predict LOS in the acute psychiatric setting. METHODS: This was a prospective, observational study. RESULTS: Overall, 385 subjects were included. The median LOS was 25 days. In the final model, six variables explained 14.6% of the variation in LOS: not having own income, psychiatric admissions in the preceding 2 years, high Clinical Global Impression and Brief Psychiatric Rating Scale scores, diagnosis of schizophrenia, and history of attempted suicide. All variables were associated with longer LOS, apart from history of attempted suicide. CONCLUSIONS: Identifying patients who will need to stay longer in psychiatric beds remains a challenge. Improving knowledge about determinants of LOS could lead to improvements in the quality of care in hospital psychiatry.